Message from NSPOI Founder President Vol.1(2) - Pradhan, Shaili (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
It is my great honor to write this message in the Journal of Nepalese Society of Periodontology and Oral Implantology, which was launched just a year back. The journal, which is published every six months, is a peer-reviewed journal and is the product of untiring work of Editorial Board. With continuous effort of the board, our aim is to get it PubMed indexed in the near future. The journal provides an opportunity to the Periodontists, researchers and faculties as well as to the other dental practitioners; both national and international, to get their work published and share knowledge. With the start of dental education in Nepal, JNSPOI can form a great platform for publications of researches carried out in the country. I am sure this journal will help to uplift the standard of care as well as academic activities in the country. I am confident enough as NSPOI brought all the Nepalese Periodontists in one platform, our JNSPOI will also bring all the Periodontal researches together. Finally, my best wishes to JNSPOI editorial board for a regular and a peer-reviewed publication.